Studi pemanfaatan fasilitas di pangkalan pendaratan ikan Amurang Kabupaten Minahasa Selatan - Fernanda M.F. Mailakay; Wilhelmina Patty; Frangky E. Kaparang; Kawilarang W.A. Masengi; Revols D.C. Pamikiran; Alfret Luasunaung (Universitas Sam Ratulangi, 2024)
It can be said that a fishing port has carried out its functions properly if all the facilities owned by the port, including the main facilities, functional facilities, and supporting facilities, are in accordance with what is expected. This research was carried out by following the descriptive method. The data taken in this study are primary data and secondary data. PPI conditions were analyzed descriptively. The steps taken to analyze the condition of the facilities are (a) taking an inventory of the types and conditions of existing facilities; (b) collect data on the size and capacity of each facility, and (c) look at the procedures for using the facility, whether it is in accordance with its function. The main facility is a facility at a fishing port that is used for mooring and berthing of fishing vessels and minimizes natural disturbances and shipping safety. The main facilities at the Amurang Fish Landing Base include the Harbor Pool Pier, Complex Roads, Mooring Poles. Functional facilities are said to be superstructures where these facilities function to increase the use value of the main facilities that can support activities at fishing ports. These facilities, among others, do not have to exist in a port, but these facilities are provided in accordance with the operational needs of the port. Functional facilities at the Amurang Fish Landing Base include Fish Auction Sites, SPDN (Solar Packed Fishermen Dealers), Cold storage, Packing Buildings Supporting facilities are facilities at fishing ports that can indirectly help and support the activities of fishing communities and even the general public Mess Office Extension Post Guard Post.